Perancangan Logo Kampanye Clean Eating Dalam Meningkatkan Pola Hidup Sehat Pasca Covid-19 di Media Sosial Instagram - Vania Victoria; Ratih Mahardika (Universitas Persada Indonesia YAI, 2023)
Currently, teenagers very often consume unhealthy foods. This of course makes the lifestyle ofteenagers to be unhealthy. An unhealthy lifestyle that is carried out continuously will of course havea negative impact on the body. Dangerous diseases can no longer threaten adults but in their teens.The main causes are unhealthy lifestyle and eating patterns, high stress levels and lack of physicalactivity such as exercising. Moreover after the Covid-19 pandemic made people inevitably have tostart healthy lifestyle in order to maintain immunity in their body. A clean eating pattern is a healthydiet by consuming natural ingredients that do not go through many processes so that the intake ofvitamins, minerals and other important substances is not lost and is well absorbed by the body.However, it turns out that there are still many people, especially teenagers, who are still not awareof the importance of maintaining health from an early age and have never done a clean eating dietbecause information is still minimal. Therefore, it is hoped that this campaign can change theawareness of teenagers about the importance of adopting a healthy lifestyle from an early age toprevent diseases that are harmful to the body